AI-Driven Methodologies for Mitigating Technical Debt in Legacy Systems - Brij Kishore Pandey; Ajay Tanikonda; Subba Rao Katragadda; Sudhakar Reddy Peddinti (Journal of Science & Technology, 2021)
Technical debt, a pervasive challenge in software engineering, significantly hampers the maintainability, scalability, and performance of legacy systems, making them susceptible to inefficiencies and high maintenance costs. As software systems age, the accumulation of ad hoc solutions, outdated dependencies, and unoptimized code creates obstacles to innovation and system resilience. This paper investigates the potential of artificial intelligence (AI)-driven methodologies to systematically mitigate technical debt in legacy systems. By leveraging AI techniques such as machine learning, natural language processing (NLP), and graph-based algorithms, the study delineates an array of approaches for automating code refactoring, dependency management, and system optimization. The proposed methodologies focus on analyzing and restructuring legacy codebases while preserving functional integrity, thus addressing key aspects of technical debt including code smells, architectural degradation, and redundant dependencies. A key contribution of this research is the exploration of machine learning models tailored for identifying and prioritizing code smells and other technical debt indicators based on historical data and system-specific heuristics. These models can autonomously suggest refactoring actions that optimize code readability, modularity, and maintainability. Additionally, the integration of NLP techniques enables the analysis of unstructured documentation and comments within codebases, extracting actionable insights to align refactoring initiatives with domain-specific requirements. Dependency management is enhanced through graph-based algorithms that analyze module interconnections, identifying circular dependencies, redundant linkages, and bottlenecks. The paper also examines system optimization through AI techniques that detect performance anomalies and propose efficient solutions to optimize computational resources and reduce latency. Practical applications of AI methodologies in mitigating technical debt are presented through case studies and experimental evaluations. These examples highlight the transformative potential of AI in improving the resilience and longevity of legacy systems. One case study demonstrates the application of reinforcement learning to evolve system architecture iteratively, reducing architectural debt and improving scalability. Another example explores automated refactoring tools augmented with AI algorithms that achieve significant reductions in code complexity and maintenance efforts. The evaluation framework considers metrics such as cyclomatic complexity, cohesion, coupling, and fault proneness to quantitatively assess the effectiveness of these methodologies. The challenges of implementing AI-driven solutions are thoroughly addressed, including issues of computational overhead, model interpretability, and resistance from stakeholders. Strategies to overcome these challenges, such as hybrid approaches combining human expertise and AI automation, are proposed to ensure the feasibility of deployment in real-world scenarios. The study also underscores the importance of ethical considerations, emphasizing transparency and accountability in AI-driven decision-making processes to avoid unintended consequences in software systems.